Lung cancer symptoms at diagnosis: results of a nationwide registry study. Issue 6 (19th November 2020) - Ruano-Raviña, Alberto; Provencio, Mariano; Calvo de Juan, Virginia; Carcereny, Enric; Moran, Teresa; Rodriguez-Abreu, Delvys; López-Castro, Rafael; Cuadrado Albite, Eugenio; Guirado, María; Gómez González, Lucía; Massutí, Bartomeu; Ortega Granados, Ana Laura; et al.
Abstract : Background: Lung cancer is currently the leading cause of cancer death. Despite its high incidence and mortality, there are few studies describing its symptoms at diagnosis broken down by tumour stage and tobacco use. Accordingly, this study was proposed to describe the frequency of the most common symptoms of non-small cell lung cancer and small cell lung cancer (SCLC) at diagnosis, with a breakdown by stage and tobacco use. Patients and methods: Cases were collected from the Spanish Thoracic Tumour Registry, a nationwide registry sponsored by the Spanish Lung Cancer Group. More than 50 hospitals recruited histologically confirmed lung cancer cases and information was gathered through personal interview plus data contained in the electronic clinical record. There were no data available on the lag between the appearance of the first symptoms and diagnosis of lung cancer. Results: A total of 9876 patients (74% male, median age 64 years) were recruited from 2016 to 2019. Of these, 12.5% presented with SCLC. Stage IV was the most frequent stage at diagnosis (46.6%), and the most frequent symptom was cough (33.9%), followed by dyspnoea (26.7%). No symptom was present in 59% of patients diagnosed in stage I; 40% of stage I patients presented with at least one symptom, while 27.7% of patients in stage IV had no symptoms at diagnosis. Cough was the most frequent symptom in SCLC (40.6%), followed by dyspnoea (34.3%). The number of symptoms was similar across the respective smoking categories in SCLC, and differences between the symptoms analysed did not exceed 7% in any case. Conclusion: The absence of the most frequent symptoms (ie, cough, pain, dyspnoea) should not lead to a decision to rule out the presence of lung cancer. A relevant percentage of stage IV patients displayed no symptoms at diagnosis.